GESTIÓN DE ACTIVOS FIJOS Y SU INCIDENCIA EN LOS INVENTARIOS DE BIENES: GAD MUNICIPAL ISIDRO AYORA - Chiquito Tigua, Gloria Pascuala (2025)
The study on fixed asset management and its impact on asset inventories at the Isidro Ayora Municipal Autonomous Government (GAD) identified problems in inventory updating, a lack of technological tools, and deficiencies in staff training. The objective was to determine how fixed asset management influences municipal inventory management. A mixed methodology was used, including descriptive, analytical, inductive, and deductive methods, in addition to surveys and interviews with 23 department heads. The results showed that 26% of staff update records monthly, 30% quarterly, and 22% annually. However, it was also identified that 22% do not update the inventory regularly, which compromises the reliability of the records. Furthermore, 35% of respondents indicated that the lack of trained personnel represents the main challenge in fixed asset management, followed by insufficient budget (26%), bureaucratic processes (22%), and insufficient technological tools (17%), highlighting structural limitations that affect municipal asset control. It is concluded that the absence of preventive maintenance policies, the limited use of management technologies, and inconsistent training affect inventory accuracy and the efficiency of asset management. Therefore, the implementation of specialized software, periodic audits, and ongoing training programs are recommended to optimize municipal asset management.